Застосування модернізованного вітчизняного устаткування в бурінні геотермальних свердловин - Вдовиченко, А.І.; Мазко, М.І.; Олійник, Є.І. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2018)
Досліджено досвід відновлення і модернізації спрацьованої вітчизняної бурової установки 1БА-15В-М та застосування її в бурінні гідротермальних свердловин, в умовах Закарпаття. Наведено перелік змін у конструкції бурової установки внесених для покращення її технічних характеристик. Для збільшення вантажопідйомності з 200 до 300 кН висоту верхньої секції щогли вкоротили на 3 м. Також було реконструйовано крон-блок, кількість роликів на ньому було збільшено з 3 до 4. Несучі конструкції щогли були зміцнено через встановлення додаткових поясів. Транспортний автомобіль МАЗ-5337 замінено на КрАЗ-257. Проаналізовано результати буріння гідротермальної свердловини цією установкою та імпортними буровими установками AGBO G750 Germany та T4WAtlasCopco в аналогічних умовах. Зафіксовано високу ефективність застосування модернізованої бурової установки порівняно з імпортними. Исследован опыт восстановления и модернизации изношенной отечественной буровой установки 1БА-15В-М и применение ее в бурении гидротермальных скважин в условиях Закарпатья. Приведенный перечень изменений в конструкцию буровой установки, внесенных для улучшения ее технических характеристик. Для увеличения грузоподъемности с 200 до 300 кН высота верхней секции мачты была укороченна на 3 м, а также реконструировано крон-блок, количество роликов на нем было увеличено с 3 до 4. Несущие конструкции мачты укреплены за счет установки дополнительных поясов. Транспортный автомобиль МАЗ-5337 заменен на КрАЗ-257. Проанализированы результаты бурения гидротермальной скважины этой установкой и импортными буровыми установками AGBO G750 Germany и T4W Atlas Copco в аналогичных условиях. Установлена высокая эффективность применения модернизированной буровой установки по сравнению с импортными. The experience of restoration and modernization of the domestic drilling rig 1BA-15V-M and its application in the drilling of hydrothermal wells in the Transcarpathian region has been researched. The list of changes in the design of the drilling rig made for improving its technical characteristics is given. To increase the carrying capacity from 200 to 300 kN, the height of the upper section of the mast was shortened by 3 m, and also the crown block was reconstructed, the number of rollers on it was increased from 3 to 4. The bearing structures of the mast were strengthened by the installation of additional belts. The transport vehicle MAZ-5337 is locked to KRAZ-257. The results of the hydrothermal drilling of this plant and the imported AGBO G750 Germany drilling rigs and Atlas Copco T4W drilling under similar conditions are analyzed. The high efficiency of the application of the modernized drilling rig as compared to the imported ones is established. The growth of the main technical and economic indicators has been achieved: the commercial speed is 1,4–1,9 times; technical – in 1,2–1,3; profitability – in 3,5. Due to a significant reduction in depreciation and fuel costs, the cost of a 1 meter well is reduced by 27%, with a 73% increase in salaries for service personnel.